Surgical treatment and results of 62 patients with epithelioid hemangioendothelioma of bone. Issue 8 (18th March 2014) - Angelini, Andrea; Mavrogenis, Andreas F.; Gambarotti, Marco; Merlino, Biagio; Picci, Piero; Ruggieri, Pietro
<x xml:space="preserve">Abstract</x> Objective Purpose of this retrospective study was (1) to evaluate overall survival and survival to local recurrence of patients with unifocal and multifocal tumor and (2) to evaluate survival to local recurrence after intralesional or wide surgery. Material and Methods We reviewed 62 patients with epithelioid hemangioendothelioma of bone, treated from 1985 to 2010. Histological sections and immunohistochemistry were evaluated. Tumor presented as unifocal in 49 patients and as multifocal in 13. Results Mean follow‐up was 9 years. Five patients (10%) with unifocal tumor progressed to multifocal. Overall survival was 92% at 10 years. Survival with unifocal tumor was significantly higher than survival with multifocal tumor. Survival to local recurrence was 76% at 10 years, significantly higher after wide resection than after intralesional surgery, while there was no statistical difference comparing unifocal and multifocal tumor. At multivariate analysis both variables showed no statistically significance. Conclusion Wide surgical excision reduces the risk of local recurrence, but functional results and morbidity need to be considered individually when defining surgical indications. Due to the risk of radiation‐induced sarcomas, radiation therapy should be reserved to those cases not amenable to wide surgery or when lesions are seated locations difficult to treat. J. Surg. Oncol. 2014 109:791–797. © 2014 Wiley Periodicals, Inc.